Retracted: A randomized prospective study to evaluate the efficacy of various topical treatment modalities in patients of alopecia areata - Manthale, Nagendra S.; Raikar, Dayanand R.; Raikar, Shrinivas R. (International Journal of Research in Dermatology, 2017)
The article "A randomized prospective study to evaluate the efficacy of various topical treatment modalities in patients of alopecia areata" is retracted by the Editor-in-Chief due to violation of the policies and practices of International Journal of Research in Dermatology. The article is retracted due to dispute in authorship. The corresponding author communicated the above article without knowledge of the principal investigator and co researchers involved in the study.